TEAMWORK CLIMATE AMONG RESIDENT PHYSICIANS IN TWO DEPARTMENTS OF AN EGYPTIAN HOSPITAL - Abdel-Aziz, Basem Farouk (International Journal For Research In Business, Management And Accounting, 2021)
Teamwork climate (TWC)is crucial for organizations’ success, including healthcare organizations. Fourteen-itemed Team Climate Inventory(TCI-14) was used to measure TWC among resident physicians in two departments in an Egyptian University Hospital. Confirmatory factor analysis via structural equation modeling and exploratory factor analysis (in a confirmatory mode) were employed to construct validate the four-factor model of TCI-14. Factorial validity was established thru global and local fit diagnostics. Convergent validity was demonstrated via adequate subscales alpha coefficients, composite reliabilities, variances extracted, and weight and significance of item loadings. Discriminant validity was verified by moderate interfactor correlations and subscales composite reliabilities were greater than average variance extracted. The validated model was utilized to calibrate and grade the level of global TWC, its four subscales and indicators, which were found to belong to the “Good” category. TWC was not contingent upon physicians' personal characteristics like, age, sex, or length of employment. Specific and all-purpose educational and training programs were recommended to improve TWC.